Variation of MgB2 growth mode and enhancement of critical current density by instantaneously 800 °C-triggered low-temperature sintering. (November 2016) - Cai, Qi; Liu, Yongchang; Guo, Qianying; Ma, Zongqing; Li, Huijun
Abstract: Instantaneous high temperature improved the low-temperature sintering efficiency of the un-doped MgB2 superconductor, and the MgB2 was rapidly synthesized at 600 °C for only 2 h. In addition to the refinement of MgO impurity particles, the sudden high temperature induced defects within the MgB2 grains, e.g. twinning crystal, and the J c performance is therefore significantly enhanced, about 2.2 × 10 3  A·cm − 2 at 4 T for bulk sample. Differed from the two-dimensional nucleation growth mode of the MgB2 grains in the high-temperature sintered un-doped sample, the low-temperature sintered MgB2 grains accord with the dislocation growth mechanism, relying on the thermal-stress-triggered twinning crystal. Graphical abstract: